A comparative analysis of foreign and domestic managers' profiles in the defense and aviation industry: The case of Turkey. Issue 3 (3rd July 2021) - Yigit, Yusuf; Bayrak, Tuncay; Ozturk, Fahrettin
Abstract: This study examines and analyzes foreign and domestic managers' profiles in the defense and aerospace industry. C-level managers and senior executives of leading defense and aerospace companies abroad are compared with senior executives in Turkey. In addition, short and long term solutions are outlined to address the skills gap that exists in the Turkish defense and aerospace industry, which has become one of the most important sectors in Turkey.